Quinine-Loaded Polymeric Nanoparticles: Validation of a simple HPLC-PDA Method to Determine Drug Entrapment and Evaluation of its Photostability - Luana Roberta Michels, Lisiane Bajerski, Tamara Ramos Maciel, Letícia Marques Colomé & , Sandra Elisa Haas & (Journal of Applied Pharmaceutical Science, 2016)
Liquid chromatographic method was developed and validated for quantitative determination of quinine in polymeric nanoparticles. The method was performed using a Waters RP-18 column using a mobile phase consisting of acetonitrile:water:triethylamine (60:40:0.01 v/v/v, and pH aqueous phase adjusted to 3.0 with phosphoric acid). The ï¬‚ow rate was 1.0 mL min-1 and the detection was achieved with a UV-PDA set at 232 nm. The response was linear over a range of 12.0 to 24.0 µg.mL-1 (r = 0.9995). The relative standard deviation values for intra-day and inter-day precision studies were less than 2% and the accuracy was 98.8% to Nc1 and 97.3% to Nc2. The samples free of quinine and quinine-loaded polymeric nanoparticles were subjected to photodegradation conditions. A considerable reduction of degradation of quinine occurred in polymeric nanoparticles. Through these results, it was clear that the nanoencapsulation of quinine protects the drug from degradation by exposure to UV-A light. The analytical method was validated according to International Conference on Harmonization Guidelines and Center for Drug Evaluation and Research.
Keywords: Nanocapsules, quinine, validation, HPLC-DAD.